A Qualitative Investigation of the Academic, Social and Emotional Needs of Graduate Students Post COVID-19: Recommendations for Graduate Faculty - Bernadowski, Carianne (Innovare Journal of Education, 2023)
This paper examines graduate students’ academic and emotional needs as they returned to campus after the abrupt shutdown of universities due to the COVID-19 pandemic. Because graduate students are unique in their mindset, learning, and needs, examining how they perceived their needs when they returned to graduate school was imperative. Based on focus groups and semi-structured interview data, three themes emerged: obstacles to balancing home, work and school, graduate students’ needs are diverse, and social and emotional needs should be at the heart of graduate studies. These findings suggest strategies to integrate more culturally relevant and social and emotional approaches to graduate teaching.